Advancements in liquid biopsy and radiology techniques for early cancer detection: A review of current methods and future directions - Alkhalaf, Abdulmohsen Khalaf Ali; Alkhateeb, Sulaiman Ali Sulaiman; Alshammari, Bushra Mana; Alharbi, Dima Ahmed; Alangari, Abdulaziz; Alfares, Musab Abdulgader; Alsharif, Khalid Abdulrahman; Alenazi, Motaeb Saqer; AlQarni, Zainab Ali; Fadan, Ola Yousef; Alabdaly, Rehaf Mesaad; Khrami, Salma Ali; et al. (International journal of health sciences, 2021)
Aim: This review explores advancements in liquid biopsy techniques and radiological imaging for early cancer detection, highlighting their potential to improve diagnosis and treatment monitoring. Methods: We analyzed various liquid biopsy technologies, focusing on circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and exosomes, along with radiological imaging techniques such as PET scans and MRI. Key methodologies include size-based enrichment, immunoaffinity-based isolation, microfluidic technologies, and advanced imaging modalities, as well as their clinical applications and limitations. Results: Liquid biopsies offer non-invasive alternatives to traditional tissue biopsies, facilitating real-time monitoring of tumor dynamics. Techniques such as droplet digital PCR and advanced microfluidic devices have enhanced the sensitivity and specificity of biomarker detection. Radiological imaging provides complementary insights into tumor location, size, and metabolic activity, enhancing the overall diagnostic accuracy. While methods like CellSearch® for CTC counting are FDA-approved, ongoing research aims to refine isolation techniques, validate biomarkers' clinical relevance, and integrate imaging findings through large-scale trials. Conclusion: The integration of liquid biopsies and radiological imaging into routine clinical practice holds promise for personalized cancer management, enabling early detection and improved treatment responses. Continued development of these technologies is crucial for enhancing patient outcomes.